2013
DOI: 10.1016/j.amjcard.2013.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Cardiac Death Among Firefighters ≤45 Years of Age in the United States

Abstract: Sudden cardiac death (SCD) is the leading cause of death in firefighters. Although on-duty SCD usually occurs in older victims almost exclusively because of coronary heart disease, no studies have examined causation across the career span. In the present retrospective case-control study, cases of SCD in young (aged ≤45 years) firefighters from the National Institute for Occupational Safety and Health fatality investigations (n = 87) were compared with 2 age- and gender-matched control groups: occupationally ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
107
1
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 106 publications
(123 citation statements)
references
References 23 publications
7
107
1
8
Order By: Relevance
“…Importantly, regression of LVH through targeted treatment has been shown to reduce the risk of cardiovascular events 39, 40, 41. Results from this study showing that cardiomegaly and LVH were fairly common among noncardiac trauma controls, who were aged <40 years on average, corroborate the findings of Yang et al12 and suggest that screening at a relatively young age may be justified for firefighters at risk of cardiomegaly.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Importantly, regression of LVH through targeted treatment has been shown to reduce the risk of cardiovascular events 39, 40, 41. Results from this study showing that cardiomegaly and LVH were fairly common among noncardiac trauma controls, who were aged <40 years on average, corroborate the findings of Yang et al12 and suggest that screening at a relatively young age may be justified for firefighters at risk of cardiomegaly.…”
Section: Discussionsupporting
confidence: 85%
“…The finding of elevated risk of SCD among firefighters with increased heart mass or wall thickness is consistent with findings from a study investigating cardiac death in a cohort of young firefighters. Yang et al12 found that the odds of duty‐related SCD in firefighters aged ≤45 years increased nearly 5‐fold in the presence of cardiomegaly. In population‐based studies, LVH has been shown to be a strong independent predictor of cardiovascular mortality, including SCD,14, 15 and the risk of SCD increased with increasing LV mass 14.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations